Atypical action updating in a dynamic environment associated with adolescent obsessive–compulsive disorder - Aleya, A Marzuki *; Vaghi, Matilde M; Conway-Morris, Anna; Kaser, Muzaffer; Sule, Akeem; Apergis-Schoute, Annemieke; Sahakian, Barbara J; Robbins, Trevor W. (Wiley, 2022)
Background: Computational research had determined that adults with obsessive-compulsive disorder (OCD) display heightened action updating in response to noise in the environment and neglect metacognitive information (such as confidence) when making decisions. These features are proposed to underlie patients' compulsions despite the knowledge they are irrational. Nonetheless, it is unclear whether this extends to adolescents with OCD as research in this population is lacking. Thus, this study aimed to investigate the interplay between action and confidence in adolescents with OCD.